2016
DOI: 10.1177/1094428116681073
|View full text |Cite
|
Sign up to set email alerts
|

The Body and the Brain: Measuring Skin Conductance Responses to Understand the Emotional Experience

Abstract: In this article, we introduce the method of measuring skin conductance responses (SCR) reflecting peripheral (bodily) signals associated with emotions, decisions, and eventually behavior. While measuring SCR is a well-established, robust, widely used, and relatively inexpensive method, it has been rarely utilized in organizational research. We introduce the basic aspects of SCR methodology and explain the behavioral significance of the signal, especially in connection with the emotional experience. Importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 142 publications
1
114
0
3
Order By: Relevance
“…With EDA data, we focused on the phasic skin conductance response (SCR) peaks as the former research had indicated that SCR peaks are strongly associated with emotional responses that are related to significant external stimulus. Hence, SCR peaks are considered more reactive to variations in experimental conditions than tonic skin conductance level (SCL) (Christopoulos, Uy, & Yap, 2016;Dawson, Schell, & Filion, 2007). After collecting the physiological data, it was first imported to Empatica E4 Connect software.…”
Section: Claim: Motivation and Emotion Regulation Is Intertwined Withmentioning
confidence: 99%
“…With EDA data, we focused on the phasic skin conductance response (SCR) peaks as the former research had indicated that SCR peaks are strongly associated with emotional responses that are related to significant external stimulus. Hence, SCR peaks are considered more reactive to variations in experimental conditions than tonic skin conductance level (SCL) (Christopoulos, Uy, & Yap, 2016;Dawson, Schell, & Filion, 2007). After collecting the physiological data, it was first imported to Empatica E4 Connect software.…”
Section: Claim: Motivation and Emotion Regulation Is Intertwined Withmentioning
confidence: 99%
“…Of particular interest for physiological biometric feedback in cognitive science are the two subsystems of the autonomic system, which is divided into the sympathetic and parasympathetic systems. The sympathetic system is supporting the stress response ('fight or flight') to threatening events; it is a central component of emotional experience and, by extension, manifests itself at the cognitive and behavioural level (Christopoulos, Uy, and Yap 2016). The sympathetic system, in turn, supports the mobilisation of the body towards appetitive or gratifying stimuli.…”
Section: Emotions and Cognitive Sciencementioning
confidence: 99%
“…The sympathetic system, in turn, supports the mobilisation of the body towards appetitive or gratifying stimuli. The typical measurable manifestation of the sympathetic system is the control, mostly involuntary, of physiological responses, such as heart rate (HR), sweating, breathing and eye blinking (Christopoulos, Uy, and Yap 2016).…”
Section: Emotions and Cognitive Sciencementioning
confidence: 99%
“…The most prevalent neurophysiological tools are galvanic skin response (GSR), cardiovascular measures, electromyography (EMG), and eye tracking (Harris et al, 2018;Mauss and Robinson, 2009;Poels and Dewitte, 2006). GSR captures activity in the sweat glands, which indicates physiological arousal and is measured by electrodes or sensors placed on the skin (Caruelle et al, 2019;Christopoulos et al, 2019;Ohme et al, 2009). GSR is suitable to, amongst other things, investigate attentional and emotional processes (Dawson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%